Real time server alert system using port scanning and reachability test functions - Muhammad Hafiz, Muhamad Hendri (2013)
Server Alert System is a monitoring tool that allows network administrator to monitor and being notified if there is issue related to the server. This system will take action by doing a quick scanning in a time cycle interval. What makes this Server Alert System possible to be developed as an effective tool is that failures in the server can be notified via SMS where the current state of the server can be determined by doing port scanning and sending the ICMP echo messages or can easily know as PING. This system is installed in the server where from the server it will send ICMP message to the gateway for connectivity checking. If the server receives a request time out message, it means the server has no connection with the gateway as well as the internet connection. This system provides several functionalities for keeping the administrator aware of problems in the server through SMS alert. When the system detects an issue, it will immediately send a warning message via SMS to the network administrator. This system will be used along with a modem to provide the SMS module. This system offers the notification that ensures the administrator to recognize there is an issue that needs attention. This Server Alert System is built using VB .Net programming language. The software that will be used is Microsoft Visual Studio 2008 to create a connection between the administrator and the server for monitoring purpose.